Adopsi XBRL, Transformasi Digital, Tax Avoidance: A Systematic Literature Review and Future Research Agenda - Sari Zawitri (Jurnal Akuntansi dan Keuangan, 2026)
This study aims to comprehensively map the dynamic interactions between the adoption of eXtensible Business Reporting Language (XBRL), digital transformation, and tax avoidance practices. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA protocol and bibliometric analysis, this study synthesizes academic literature from 2015 to 2025 to uncover the paradigm shift from mere formal compliance toward digital institutional change. Key findings highlight the paradoxical phenomenon of the "licensing effect," wherein companies with high Corporate Social Responsibility (CSR) performance tend to leverage their social reputation as a shield to engage in aggressive tax avoidance amidst heightened digital scrutiny. Furthermore, this study proposes an integrative "Triple-Dimension" framework and asserts that technologies such as XBRL and blockchain are not universal standalone solutions, but rather instruments whose effectiveness relies heavily on infrastructure readiness and institutional integrity within each jurisdiction.